Impacts of Global Warming in Natural Science: Evaluate Elementary Student’s HOTS and PEB in Environmental Education - Ilmi Zajuli Ichsan; Anggit Merliana; Eva Dwi Kumala Sari (Jurnal Penelitian Pendidikan IPA, 2023)
Global warming is a hot topic in various countries. The impacts of global warming are felt through the decrease in health. Handling the issue requires Higher Order Thinking Skills (HOTS) and Pro-Environmental Behavior (PEB) in environmental education. Elementary school students need to contribute to preventing global warming. The research aims to describe the HOTS and PEB of elementary school students on the topic of the impacts of global warming. The research used a descriptive method. Research instruments are used to measure HOTS and PEB and are disseminated using Google Forms. The research results indicate that the HOTS score of elementary school students is still in a very low category (21.32), whereas their PEB score is in a high category (80.65). Learning media can be developed in future research to improve students’ HOTS regarding the impacts of global warming. This research concludes that HOTS and PEB of students in impact of global warming must be improve. The limitation of this study is that the scope of this research is still very limited because it has not yet carried out media development for students at school